2010
DOI: 10.1638/2009-0244.1
|View full text |Cite
|
Sign up to set email alerts
|

Elodontoma in Captive Southern Red-Backed Voles (Myodes gapperi)

Abstract: Five southern red-backed voles (Myodes gapperi) of the first generation of a wild-caught breeding colony were presented with lesions at the maxillary incisors consistent with elodontoma. The affected animals had a history of chronic weight loss, were >16 months of age, and were siblings. Radiographs of the head showed multiglobular to irregularly outlined mineral opacity masses at the apices of the maxillary incisors. On necropsy, maxillary incisor teeth were not grossly visible, and a gingival ulceration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Pseudo-odontoma was considered appropriate for some of the dysplastic changes, particularly the abnormal matrigenesis, observed at the molar apices but not for the masses of markedly disrupted, haphazardly organized and proliferative odontogenic epithelium. Despite these challenges, the gross and histopathologic features here are very similar to those described in rat-like and squirrel-like rodents, 1,2,13,22 rabbits, 17 and other voles 29 though less proliferative and destructive than those described in guinea pigs and degus. 2,4,16,19,23 Observations in CSF-1-deficient, 14 Snx10-deficient and bisphosphonate-treated (personal observations, D. Imai) osteopetrotic rodents have confirmed that microtraumatic disruption and fragmentation of odontogenic epithelium by bone can produce isolated and disorganized islands of proliferative odontogenic epithelium that can subsequently proliferate into odontoma-like masses.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Pseudo-odontoma was considered appropriate for some of the dysplastic changes, particularly the abnormal matrigenesis, observed at the molar apices but not for the masses of markedly disrupted, haphazardly organized and proliferative odontogenic epithelium. Despite these challenges, the gross and histopathologic features here are very similar to those described in rat-like and squirrel-like rodents, 1,2,13,22 rabbits, 17 and other voles 29 though less proliferative and destructive than those described in guinea pigs and degus. 2,4,16,19,23 Observations in CSF-1-deficient, 14 Snx10-deficient and bisphosphonate-treated (personal observations, D. Imai) osteopetrotic rodents have confirmed that microtraumatic disruption and fragmentation of odontogenic epithelium by bone can produce isolated and disorganized islands of proliferative odontogenic epithelium that can subsequently proliferate into odontoma-like masses.…”
Section: Discussionsupporting
confidence: 69%
“…2,6,11 Elongation of the apices of elodont teeth, whether incisor or molar teeth, is well recognized as an acquired dental disease in rabbits and a variety of pet rodents 2 and has been previously described in other arvicoline rodents. 11,12,15,18,29,30 The proposed pathophysiologic mechanisms vary from being a heritable trait 14,15,18 to an acquired disease process 1,2,14 to a multifactorial combination of both. 11,12,29…”
mentioning
confidence: 99%
See 3 more Smart Citations